2024
DOI: 10.1039/d3ta07107c
|View full text |Cite
|
Sign up to set email alerts
|

Progresses on high-entropy nano-catalysts for electrochemical energy conversion reactions

Lihua Zhang,
Tong Wu,
Yinbo Zhan
et al.

Abstract: Nanostructured high-entropy materials (HEMs) have garnered significant attention as a burgeoning class of materials in the field of electrocatalysis, due to their exceptional structural and functional properties. Many milestones have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 164 publications
0
2
0
Order By: Relevance
“…206 Highentropy metal phosphides (HEMPs), integrating multiple metal elements, further enhance electrocatalytic performance by providing compositional flexibility and multiple active sites (Figure 9). 207 Notably, HEMPs have emerged as ideal candidates for water splitting electrocatalysis, as demonstrated by Lu et al's synthesis of NiCoFeMnCrP nanoparticles, which exhibited remarkable performance in both OER and hydrogen evolution reaction (HER). 209 Mu et al also demonstrated the potential of HEMPs, synthesized through a eutectic solvent method, with uniform elemental distribution facilitating strong synergistic effects and enhanced electrocatalytic performance, reaffirming the promising outlook of HEMPs in electrochemical water splitting applications (Figure 10).…”
Section: Alkaline Electrolytementioning
confidence: 99%
See 1 more Smart Citation
“…206 Highentropy metal phosphides (HEMPs), integrating multiple metal elements, further enhance electrocatalytic performance by providing compositional flexibility and multiple active sites (Figure 9). 207 Notably, HEMPs have emerged as ideal candidates for water splitting electrocatalysis, as demonstrated by Lu et al's synthesis of NiCoFeMnCrP nanoparticles, which exhibited remarkable performance in both OER and hydrogen evolution reaction (HER). 209 Mu et al also demonstrated the potential of HEMPs, synthesized through a eutectic solvent method, with uniform elemental distribution facilitating strong synergistic effects and enhanced electrocatalytic performance, reaffirming the promising outlook of HEMPs in electrochemical water splitting applications (Figure 10).…”
Section: Alkaline Electrolytementioning
confidence: 99%
“…High-entropy metal phosphides (HEMPs), integrating multiple metal elements, further enhance electrocatalytic performance by providing compositional flexibility and multiple active sites (Figure ). …”
mentioning
confidence: 99%